CO2 Fixation via epoxide cycloaddition with a highly active and stable MOF-808/GO composite catalyst - Qu, Zhengyan; Zhou, Minghui; Zhang, Jiuxuan; Jiang, Hong; Tang, Zhenchen; Xing, Weihong; Chen, Rizhi (Separation and purification technology, 2025)
Through incorporating GO in the synthesis of MOF-808, a series of MOF-808/GO-X composite materials were prepared. The pre-coordination between the oxygen-containing groups on GO and Zr ions facilitates the formation of defective Zr sites (as catalytic Lewis acid) and the dispersion of MOF-808, thus enhancing the accessibility of catalytic sites and mass transfer. The MOF-808/GO-100 exhibits excellent catalytic performance in CO2 cycloaddition without adding solvent and co-catalyst, reaching 2 times higher activity than pristine MOF-808. [Display omitted] •The incorporation of GO enhances MOF-808 dispersion and active site accessibility.•The interaction of GO and MOF-808 promotes mass transfer with mesopore formation.•GO competes with ligands for Zr coordination thus creates more defective Zr sites.•The presence of GO introduces hydroxyl groups as hydrogen bonding donors.•MOF-808/GO-100 shows excellent performance in the CO2 cycloaddition reaction. The CO2 cycloaddition reaction effectively mitigates the greenhouse effect while producing high-value cyclic carbonates. Metal-organic frameworks (MOFs) have shown promise for CO2 cycloaddition with epoxides; however, the aggregation of MOFs due to high surface energy hinders mass transfer and catalytic performance. By pre-coordinating graphene oxide (GO) to regulate the dispersion of MOF-808, the resulting MOF-808/GO-100 composite catalyst exhibits twice the activity of pristine MOF-808, achieving 92.6% conversion of epichlorohydrin (ECH) with 98.2% selectivity to ECH carbonate without adding any co-catalysts. The incorporation of GO introduces numerous hydroxyl groups on the catalyst surface, serving as hydrogen bonding donors. The oxygen-containing groups on GO can compete with ligands for Zr coordination, generating defective Zr sites. The synergistic effect between defective Zr sites and hydrogen bonding donors collectively promotes epoxide opening. Notably, GO correspondingly enhances the dispersion of MOF-808 and induces mesopore formation through its stacking effect at the interface with MOF-808. Across various epoxide cycloaddition reactions, MOF-808/GO-100 consistently demonstrated optimal performance and maintained high stability over multiple reaction cycles.